Northwest history. Mining. Leases & options. 1927-10-22 (1927)
Tuscumbia mine sells at $100,000. Idora also taken over by Alcorn and his Seattle associates. A. F. Alcorn and associates of Seattle have taken a lease and bond on the property of the Tuscumbia Mining company on Beaver creek in the Coeur d'Alenes and it is said they also have secured the adjoining Idora group, in which Spokane men are interested. The deal for the Tuscumbia is on a basis of $100,000 and has been approved by the directors. Payments begin July 1, 1928, but in the meantime the new interests will do extensive work. A special meeting of the stockholders will be called to ratify the deal.